Removal of Cr(VI) using a novel adsorbent modification. Ultrasonic method with apricot kernel shells - Kalipci, Erkan; Namal, Osman Onder (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
Raw apricot kernel shells (AKS) and ultrasound-modified apricot kernel shells were used as adsorbents for the removal of Cr(VI) from aqueous solutions. For raw and modified AKS, the experimental data well fitted to the Langmuir isotherm and adsorption kinetics was suited to pseudo-second order kinetic model indicating chemisorption as the rate-limiting step. For raw and modified AKS, maximum adsorption capacities obtained from the Langmuir adsorption model were 6.5 mg/g and 9.9 mg/g, respectively. Maximum Cr(VI) adsorption was obtained at a pH 2 and optimum stirring speed was determined as 250 rpm. After ultrasound modification, an increase for Cr(VI) adsorption was observed. Raw AKS as low-cost natural biomaterial can be preferred for the removal of Cr(VI) when compared to other adsorbents. Ultrasonic modification can be used to improve the efficiency of Cr(VI) removal
Environment Protection Engineering. Vol. 44, 2018, nr 3, s. 79-92
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma